Fiscal Capacity and State Formation in Francophone West Africa, 1850-2010 - Jens Andersson (African Economic History Network (AEHN), 2015)
This study contributes to African state and fiscal history by presenting a detailed comparison of the evolution of fiscal capacity in four countries in francophone West Africa – Benin, Côte d'Ivoire, Niger and Senegal - over both the colonial and independent periods. While common patterns and persistence can be observed it is instead the unique fiscal pathways of the individual countries that stand out. These pathways can only be understood by analyzing how the underlying economic and political factors of each country develop over time. The importance of the colonial heritage in the development of fiscal capacity for individual countries should therefore not be overemphasized.
Keywords: N17; N27; N47; N97; 330; Africa; economic history; fiscal capacity; francophone